1983
DOI: 10.1073/pnas.80.7.1897
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequence of a French bean storage protein gene: Phaseolin

Abstract: The complete nucleotide sequences of the gene and the mRNA coding for a specific phaseolin type French bean major storage protein have been determined. Comparison of these sequences reveals a phaseolin gene structure consisting of 80 base pairs (bp) of 5' untranslated DNA, 1,263 bp of protein-encoding DNA which is interrupted by five intervening sequences (IVSI,72 bp; IVS2, 88 bp; IVS3, 124 bp; IVS4, 128 bp; and IVS5, 103 bp), and 135 bp of 3' untranslated DNA. Sequences characteristic of eukaryotic promoters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(119 citation statements)
references
References 29 publications
6
112
1
Order By: Relevance
“…A common motif (-LHKP) is found at the C terminus of both the rice and castor sPLA 2 a sequences, constituting a putative ER retention signal (Singh et al, 2012). RcsPLA 2 a and RcsPLA 2 b were cloned from a castor endosperm complementary DNA (cDNA) library, introduced into the expression vector pGate-DsRed-Phas (Lu et al, 2006), and expressed under the control of the seed-specific phaseolin promoter (Slightom et al, 1983) in the Arabidopsis CL37 line. CL37 is an Arabidopsis line expressing RcFAH12 and accumulating 17% HFAs, including ricinoleic acid and densipolic acid (12-hydroxy-octadec-cis-9,15-enoic acid [18:2-OH]; Lu et al, 2006).…”
Section: Phylogenetic and Sequence Analyses Of Splamentioning
confidence: 99%
“…A common motif (-LHKP) is found at the C terminus of both the rice and castor sPLA 2 a sequences, constituting a putative ER retention signal (Singh et al, 2012). RcsPLA 2 a and RcsPLA 2 b were cloned from a castor endosperm complementary DNA (cDNA) library, introduced into the expression vector pGate-DsRed-Phas (Lu et al, 2006), and expressed under the control of the seed-specific phaseolin promoter (Slightom et al, 1983) in the Arabidopsis CL37 line. CL37 is an Arabidopsis line expressing RcFAH12 and accumulating 17% HFAs, including ricinoleic acid and densipolic acid (12-hydroxy-octadec-cis-9,15-enoic acid [18:2-OH]; Lu et al, 2006).…”
Section: Phylogenetic and Sequence Analyses Of Splamentioning
confidence: 99%
“…Three TATA box sequences are located upstream from the mRNA cap at positions -28, -37 and -39. Slightom et al [25] postulated that the sequence at -28 was likely to be the most important in driving high expression from the phas promoter; this was later confirmed by Grace et al [40] who used an in vitro transcription system that revealed that the sequence and spacing of the TATA box elements are critical for accurate initiation from the -phaseolin promoter. The A+T content of the introns is similar to that in soybean proteins, but is considerably higher than those of non-plant species.…”
Section: Phaseolin Gene Structurementioning
confidence: 56%
“…Zein, the major storage prolamin storage protein of maize [42] is encoded by a family of highly similar genes bearing a TATA motif at -32, similar to that of most eukaryotes. In contrast, the zein CCAT sequence is located at -112 bp [25]. The hexanucleotide poly (A) addition signal sequence AATAAA is located 16 bp 5' to the first nucleotide of poly (A).…”
Section: Phaseolin Gene Structurementioning
confidence: 98%
See 2 more Smart Citations